Toward Intelligent Caching in DSR Protocols: Route Compression, Hierarchical Structures, and Link-Aware Optimization in MANETs - Ammar Kareem Obaid; Mohd Ezanee Bin Rusli; Salman Yussof (IEEE Access)
Mobile Ad Hoc Networks (MANETs) are decentralized, infrastructure-less wireless systems that rely heavily on efficient routing protocols due to their dynamic and resource-constrained nature. Dynamic Source Routing (DSR) is widely adopted for such environments; however, it suffers from notable limitations, including cache saturation, memory inefficiencies, and lack of link quality awareness. These weaknesses reduce performance in high-mobility or large-scale scenarios and limit the reliability of DSR in real-world applications like military or disaster recovery networks. Motivated by these challenges, this paper proposes a comprehensive enhancement to DSR through intelligent caching strategies to improve scalability, energy efficiency, and route reliability. The proposed model introduces a dynamic route compression technique that reduces route size by eliminating redundant intermediate nodes. It also incorporates a hierarchical caching scheme where clusters managed by energy-aware Cluster Heads (CHs) distribute cache responsibilities, thereby improving scalability and reducing overhead. In addition, link quality metrics such as residual energy and link duration are integrated into route selection, enabling more stable and energy-efficient communication paths. Simulations using NS-2 across varying network sizes (50, 75, 100 nodes) revealed that the enhanced DSR significantly improves key performance metrics such as Packet Delivery Ratio (PDR), routing overhead, cache hit rate, and energy consumption. Route compression alone yielded a 14.3 PDR improvement and 21% reduction in overhead, while the hierarchical approach further optimized network performance. These results confirm the feasibility and effectiveness of the proposed enhancements, addressing longstanding gaps in traditional DSR implementations and laying a foundation for scalable and intelligent MANET routing protocols.